Aspek Potensi Hambatan Aktivitas Fisik Tingkat Stres, Motivasi, Dan Infrastruktur Terhadap Kondisi Fisik - Nugroho, Edo Wisnu; Akhiruyanto, Andry; Putra, Ranu Baskora Aji (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to analyze potential barriers to physical activity in the aspects of stress levels, motivation, and infrastructure for physical activity. The method used is correlation and cross-sectional design. This research used research subjects as many as 190 police officers in the academy environment. The data collected includes stress levels, motivation, infrastructure, and physical condition. The analytical data used is the correlation test and determination coefficient test. Potential barriers physical activity to the stress level influence physical condition by 60%, potential barriers to the motivation aspect influence physical condition by 30%, and infrastructure aspects influence physical condition by 9%. Potential barriers aspects of stress levels, motivation and infrastructure together influence physical condition by 83%. It was concluded that the higher the prevalence of potential barriers, the lower the level of physical condition. Key words: Barriers, Police Officers, Physical Condition, Stress Level, Motivation